Phylogenetic conservation of Trop-2 across species—rodent and primate genomics model anti-Trop-2 therapy for pre-clinical benchmarks - Guerra, Emanuela; Trerotola, Marco; Relli, Valeria; Lattanzio, Rossano; Boujnah, Khouloud; Travali, Nicole; Moschella, Antonino; Todaro, Paolo; Pierdomenico, Laura; Di Pietro, Roberta; Tinari, Nicola; Alberti, Saverio (Frontiers in Genetics, 2024)
A phylogenetic conservation analysis of Trop-2 across vertebrate species showed a high degree of sequence conservation, permitting to explore multiple models as pre-clinical benchmarks. Sequence divergence and incomplete conservation of expression patterns were observed in mouse and rat.Primate Trop-2 sequences were found to be 95%-100% identical to the human sequence. Comparative three-dimension primate Trop-2 structures were obtained with AlphaFold and homology modeling. This revealed high structure conservation of Trop-2 (0.66 ProMod3 GMQE, 0.80-0.86±0.05 QMEANDisCo scores), with conservative amino acid changes at variant sites. Primate TACSTD2/TROP2 cDNAs were cloned and transfectants for individual ORF were shown to be efficiently recognized by humanized anti-Trop-2 monoclonal antibodies (Hu2G10, Hu2EF).Immunohistochemistry analysis of Macaca mulatta (rhesus monkey) tissues showed Trop-2 expression patterns that closely followed those in human tissues. This led us to test Trop-2 targeting in vivo in Macaca fascicularis (cynomolgus monkey). Intravenously injected Hu2G10 and Hu2EF were well tolerated from 5 to 10 mg/kg. Neither neurological, respiratory, digestive, urinary symptoms, nor biochemical or hematological toxicities were detected during 28-day observation. Blood serum pharmacokinetic (PK) studies were conducted utilizing anti-idiotypic antibodies in capture-ELISA assays. Hu2G10 (t1/2=6.5 days) and Hu2EF (t1/2=5.5 days) were stable in plasma, and were detectable in the circulation up to three weeks after the infusion. These findings validate primates as reliable models for Hu2G10 and Hu2EF toxicity and PK, and support the use of these antibodies as nextgeneration anti-Trop-2 immunotherapy tools.